THE APPLICATION OF MENU APPETIZER BASED ON MENU ENGINEERING TO INCREASE SELLING VOLUME IN EL PATIO RESTAURANT, SOL BEACH HOUSE BENOA BALI - I Gusti Ngurah Dhyangga Prawesta Putra; Ida Ayu Elistyawati; I Made Darma Oka (Journal of Applied Sciences in Travel and Hospitality, 2018)
Restaurant is a business that plays an essential role in tourism. The management of restaurant is always attempting to increase the sales menu by evaluating the offered menu in order to gain maximum profits. This article focuses on: (1) The application of menu appetizer based on menu engineering in El–Patio Restaurant and (2) its attempts to increase the sales volume of appetizer menu in El–Patio Restaurant. Data was collected by using observation, documentation, and intensive interviews method. Data analysis used in this research is menu engineering analysis. The result showed that from 21 items of appetizer menu analyzed, there were 47,6% or 10 menus with a high popularity level while 52,4% or 11 menus were on the low popularity level. Meanwhile, there were 7 menu items or 33,3% that has the highest contribution margin and 66,7% or 14 items with the lowest contribution margin. Then, from 21 items of appetizer menu analyzed, 28,6% or 6 menu items are categorized as star, 19% or 4 items are categorized as plowhorse, 4,8% or 1 item is categorized as challenge and 47,6% or 10 items are categorized as dog. Attempts that can be done by the management of F&B Department, Sol Beach House Benoa Bali is to improve the menu quality, promote th menu , suppress the production cost, removing unfavorable menu and develop a new menu. It is recommended for the management of F&B Department, Sol Beach House Benoa Bali to evaluate the menus with the analysis of menu engineering at least every 3 months.